2009
DOI: 10.1016/s0377-1237(09)80091-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Crestal Bone Loss along Two Implant Crest Module Designs

Abstract: Crestal bone loss was less among implants with rough collar design as compared to smooth collar design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 6 publications
1
28
0
Order By: Relevance
“…Eight of the selected studies [ 3 , 15 , 21 25 , 27 ] evaluated the survival rates in relation to the type of collar surface characterization. Radiographic evaluation of MBL was performed by means of periapical radiographs in 9 studies [ 3 , 15 , 20 24 , 27 , 28 ], panoramic radiographs in two studies [ 19 , 25 ], and maxillofacial CT in one study [ 26 ]. Rough and machined collars were considered in 7 studies [ 15 , 20 , 21 , 23 , 24 , 26 , 28 ]; while machined and microthreaded neck implants were installed in seven studies [ 3 , 15 , 19 , 21 , 22 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight of the selected studies [ 3 , 15 , 21 25 , 27 ] evaluated the survival rates in relation to the type of collar surface characterization. Radiographic evaluation of MBL was performed by means of periapical radiographs in 9 studies [ 3 , 15 , 20 24 , 27 , 28 ], panoramic radiographs in two studies [ 19 , 25 ], and maxillofacial CT in one study [ 26 ]. Rough and machined collars were considered in 7 studies [ 15 , 20 , 21 , 23 , 24 , 26 , 28 ]; while machined and microthreaded neck implants were installed in seven studies [ 3 , 15 , 19 , 21 , 22 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Different implant neck designs have been proposed in order to stabilize the bone-implant contact [ 19 , 20 , 26 , 29 , 37 ]. The smooth neck implants result in reduced plaque accumulation and thus presumably prevent peri-implantitis [ 15 , 16 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients were recalled for second stage surgery after 3-6months [10,11]. A conservative incision was made on the soft tissue over the cover screw and healing abutment was placed.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, researchers gradually discovered that the machined necks led to crestal bone loss during early functional loading after several decades of installation procedures. [14][15][16][17] Additionally, some scholars reported that the micro-roughened surface did not increase plaque accumulation, nor did it lead to crestal bone loss; however, the surface was reportedly more conducive for forming a wide and tightly attached closed loop of connective tissue. [18][19][20][21] Therefore, the suitability of machined and micro-roughened surfaces for the transmucosal area is currently debated.…”
mentioning
confidence: 99%